2017
DOI: 10.1016/j.appet.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive electromyography-based eating detection in daily life: A new tool to address underreporting?

Abstract: Research on eating behavior is limited by an overreliance on self-report. It is well known that actual food intake is frequently underreported, and it is likely that this problem is overrepresented in vulnerable populations. The present research tested a chewing detection method that could assist self-report methods. A trained sample of 15 participants (usable data of 14 participants) kept detailed eating records during one day and one night while carrying a recording device. Signals recorded from electromyogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Also, we did not assess participants’ knowledge about food healthiness and which aspects (e.g., calorie content) they considered. In order to corroborate the current results, objective assessments of eating behaviour (e.g., electromyography‐based chewing or swallowing activity or doubly labelled water method; e.g., see Blechert et al ., ) might aid in obtaining a rough amount of calorie intake as one approach to healthy eating. To measure healthy eating via the amount of intake of different food categories (e.g., vegetables vs. sweets), assessing pictures of the participants’ foods or detailed food diaries could aid in more objectively clustering foods in healthy versus unhealthy.…”
Section: Discussionmentioning
confidence: 97%
“…Also, we did not assess participants’ knowledge about food healthiness and which aspects (e.g., calorie content) they considered. In order to corroborate the current results, objective assessments of eating behaviour (e.g., electromyography‐based chewing or swallowing activity or doubly labelled water method; e.g., see Blechert et al ., ) might aid in obtaining a rough amount of calorie intake as one approach to healthy eating. To measure healthy eating via the amount of intake of different food categories (e.g., vegetables vs. sweets), assessing pictures of the participants’ foods or detailed food diaries could aid in more objectively clustering foods in healthy versus unhealthy.…”
Section: Discussionmentioning
confidence: 97%
“…experimenter measured weight and food protocols. Novel assessment tools like (e.g., electromyogram-based eating detection; Blechert, Liedlgruber, Lender, Reichenberger, & Wilhelm, 2017) would provide objective and real-time on eating and, crucially -chewing behavior. Third, the mostly female sample might limit the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies used multiple self-report methods to collect ground-truth eating activity. Six studies used both an eating or activity log in addition to a marker/push button 18,36,40,41,43,45 . Two studies, both reported in Mirtchouk et al 52 , had participants use a combination of eating logs, voice notes ("spoken annotations"), and self-taken photos at the start and end of meals.…”
Section: Ground-truth Methodsmentioning
confidence: 99%
“…The second most frequently utilized wearable sensor was a gyroscope (device that determines orientation) (N = 15) 33,38,39,46,48,49,51,53,[56][57][58] , followed by a microphone (N = 8) 34,35,47,52,54,60,61 , a piezoelectric sensor (N = 7) 18,40-42,44,45 , a RF transmitter and receiver (N = 6) 18,40,41,44,45 , and a smartwatch camera (N = 5) 56,57 (Table 2). EMG electrodes 36,63,64 , a motion sensor 52 , and an infrared proximity sensor 33,34,37 were used in three studies each. Wearable video cameras 50,55 and GPS 53,54 were used in two studies.…”
Section: Wearable Sensorsmentioning
confidence: 99%